Ambulatory intracranial pressure in humans: ICP increases during movement between body positions - Eleanor M. Moncur; Linda D'Antona; Amy L. Peters; Graziella Favarato; Simon Thompson; Celine Vicedo; Lewis Thorne; Laurence D. Watkins; Brian L. Day; Ahmed K. Toma; Matthew J. Bancroft (Brain and Spine)
Introduction: Positional changes in intracranial pressure (ICP) have been described in humans when measured over minutes or hours in a static posture, with ICP higher when lying supine than when sitting or standing upright. However, humans are often ambulant with frequent changes in position self-generated by active movement. Research question: We explored how ICP changes during movement between body positions. Material and methods: Sixty-two patients undergoing clinical ICP monitoring were recruited. Patients were relatively well, ambulatory and of mixed age, body habitus and pathology. We instructed patients to move back and forth between sitting and standing or lying and sitting positions at 20 s intervals after an initial 60s at rest. We simultaneously measured body position kinematics from inertial measurement units and ICP from an intraparenchymal probe at 100 Hz. Results: ICP increased transiently during movements beyond the level expected by body position alone. The amplitude of the increase varied between participants but was on average ∼5 mmHg during sit-to-stand, stand-to-sit and sit-to-lie movements and 10.8 mmHg [95%CI: 9.3,12.4] during lie-to-sit movements. The amplitude increased slightly with age, was greater in males, and increased with median 24-h ICP. For lie-to-sit and sit-to-lie movements, higher BMI was associated with greater mid-movement increase (β = 0.99 [0.78,1.20]; β = 0.49 [0.34,0.64], respectively). Discussion and conclusion: ICP increases during movement between body positions. The amplitude of the increase in ICP varies with type of movement, age, sex, and BMI. This could be a marker of disturbed ICP dynamics and may be particularly relevant for patients with CSF-diverting shunts in situ.